The use of thermal imaging to evaluate body temperature changes of athletes during training and a study on the impact of physiological and morphological factors on skin temperature - Chudecka, M.; Lubkowska, A. (Human Movement, 2012)
The aim of this study was to assess the temperature changes of selected body surfaces (the arm and forearm) as a response to 90-minute physical exercise as well as to analyze the impact of physiological and morphological factors on the dynamics of temperature change. Methods. A study group that consisted of 12 professional volleyball players was subjected to endurance training which lasted 90 minutes. Numerous physiological and morphological factors were measured, with mean temperatures registered from the body surface of the upper extremities before, immediately after, and ten min after physical effort by a thermal camera (SC500 ThermaCAM camera) at room temperature. Results. After physical exercise, a fall in skin temperature resulting from prolonged sweating during the dynamic exercise tests was observed. The temperature changes in volleyball players, recorded in a series of tests, were found to be larger on the front surfaces of their upper extremities when compared to the rear. In addition, statistically significant positive correlation between maximum oxygen uptake (VO2max) and %HRmax, calculated with the decrease in skin temperatures, was found. Conclusions. The strong and statistically significant influence of maximum oxygen uptake on the drop in surface temperature of the upper extremities (arm and forearm) immediately after the exercise indicates that thermography can be used as an additional, non-invasive method that provides information on a player's fitness level in comparison to other athletes.